Key differences on the compaction response of natural and glass fiber preforms in liquid composite molding - Francucci, Gaston Martin (2013)
In the present work, the effects of fiber structure and fluid absorption on the compaction behavior of jute woven fabrics and sisal mats were analyzed and compared with the response of glass fiber mats. It was found that the fiber content that can be achieved with a certain compaction pressure is lower in the case of natural fiber preforms. In addition, due to the hollow structure of these natural fibers, jute and sisal preforms suffered larger permanent deformation than glass fiber preforms after the compressive loading cycle. In addition, it was found that fluid absorption reduced the compaction pressure in natural reinforcements due to fiber softening. These phenomena were not observed in glass fiber mats.